Chemical characteristics of soil cultivated with vine and submitted to nitrogen and organic fertilization at the semiarid of the Rio Grande do Norte State, Brazil - Lima, Franciezer Vicente; Mendonça, Vander; Alves, Anderson Araújo; Pereira, Eduardo Castro; Pereira, Gustavo Alves; Farias, Wagner César de (Comunicata Scientiae, 2019)
A probable reason for the scarce levels of N in the soils of the semi-arid regions would be the low levels of organic matter in these soils. In this way, the aim of the present study was to evaluate the effects of nitrogen and organic fertilization and their interaction on chemical properties of soils cultivated with ‘Isabel Precoce’ vines in the semiarid oh the Rio Grande do Norte State, Brazil. The experiment was carried out at the Experimental Farm of the Federal Rural University of the Semi-arid Region, in Mossoró, RN. The soil in the area is classified as a Distrofic Red Argisol with sandy texture. The research was carried out in two cycles of grape production. The experiment was accomplish in a randomized blocks design, with six repetitions, in a 5 x 2 factorial scheme, corresponding to 5 doses of nitrogen fertilization (0, 30, 60, 90 and 120 kg ha-1), in the absence and presence of organic fertilization 0 and 20 m3 ha-1, bovine manure). Samples of the 0-20 cm layer were collected for the evaluation of macro and micronutrient contents, pH, electric condutivity, organic matter and sum of bases. The N and organic fertilization doses influenced the chemical atributes evaluated. The interaction between nitrogen and organic fertilizer resulted in an increase in nutrient, organic matter and sum of bases content. N doses were responsible for reducing pH levels, resulting in higher amounts of nutrients availability.